Do telejornal ao Youtube: uma análise da linguagem jornalística do programa Vale Agrícola - Carniel, Emerson Heitor (2020)
This research aims to carry out an analysis of the journalistic language of two editions of the program Vale Agrícola, broadcast weekly on YouTube. The study seeks to unveil which elements of the journalistic language of the Vale Agrícola channel are coming from the traditional TV news. The article is structured around two main theoretical concepts: television news language (DUARTE, 2000) and narrative structure of the text television (EMERIM, 2012). The methodology follows the precepts of content analysis (BARDIN, 2016).